KLAUSULA ARBITRASE YANG DICANTUMKAN PADA AKTA NOTARIS SEBAGAI DASAR PENYELESAIAN SENGKETA MELALUI ARBITRASE - Laksmi Mahadewi, I Gusti Agung Ika; W.Wp.M.S, I.G.N. Wira (Jurnal Ilmiah Raad Kertha, 2025)
Along with the development of the times, Alternative Dispute Resolution has begun to receive more attention in Indonesia because the era of globalization requires a dispute resolution system that can adjust the pace of economic and trade development towards a free market and free competition and for that there must be an institution that accommodates it.